2008
DOI: 10.1111/j.1469-7998.2008.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and allometry of genitalia in males and females of a social African ground squirrel with high polygynandry

Abstract: The few studies that have looked at genital allometry in mammals have typically shown a positively allometric relationship with body size and high coefficients of variation. Cryptic female choice, sexual conflict or sperm competition are mechanisms underlying genital evolution and as these are not mutually exclusive, they are often difficult to disentangle. In addition, these mechanisms are affected by both male and female social structure and/or mating strategies and, as such, pre-and post-copulatory behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 49 publications
(95 reference statements)
2
20
0
Order By: Relevance
“…This is in agreement with the findings of previous studies of genital allometry in mammals conducted by Manjerovic et al (2008), Kinahan et al (2007Kinahan et al ( , 2008, Tasikas et al (2007) and particularly Lüpold et al (2004) where the role of the penis as a good genes indicator was mooted. We support the sexual selection hypothesis for several reasons (adapted from Kinahan et al, 2007), even though positive allometry of both male and female genitalia was not found for A. hottentotus.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This is in agreement with the findings of previous studies of genital allometry in mammals conducted by Manjerovic et al (2008), Kinahan et al (2007Kinahan et al ( , 2008, Tasikas et al (2007) and particularly Lüpold et al (2004) where the role of the penis as a good genes indicator was mooted. We support the sexual selection hypothesis for several reasons (adapted from Kinahan et al, 2007), even though positive allometry of both male and female genitalia was not found for A. hottentotus.…”
Section: Discussionsupporting
confidence: 83%
“…In this study we found positive allometry and a high CV in the genitalia of male Amblysomus hottentotus, which is typical of sexually selected traits and has been supported by previous studies on mammals (Miller & Burton, 2001;Lüpold et al, 2004;Kinahan et al, 2007;Manjerovic et al, 2008). In the first study of allometry performed on female mammals, Kinahan et al (2007) found positive allometry and a high CV for female reproductive tract length in Bathyergus suillus.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Condition also has been linked to variations in sperm quantity and/or quality with the assumption that better body condition leads to producing more sperm (Pitnick et al 2009). Although no differences in size of testes have been detected between tactics (Scantlebury et al 2008), male X. inauris show high amounts of sperm competition (Manjerovic et al 2008), which is common in species that multiply mate. Given the fact that the most estruses fail to produce any offspring and those that do average a single offspring, the likelihood of multiple paternity is low.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, males compete predominantly via precopulatory competitive searching (Waterman 1995(Waterman , 1998 and sperm competition (Manjerovic et al 2008) although additional behaviors might influence reproductive success. Male X. inauris reach reproductive maturity between 8 and 10 months, at which point they either disperse and join a roving all-male band or delay dispersal and remain in their natal burrow for up to 4 years (Waterman 1995(Waterman , 1997Scantlebury et al 2008).…”
mentioning
confidence: 99%